Islam and the West a love story? - Mukherjee, Sumita; Zulfiqar, Sadia (Cambridge Scholars Publishing, 2015)
Islam, like the West, is not a homogenous monolith. These depictions of Islam suggest that the relationship between Islam and the West is, and has always been, one of hostility and hatred. However, the authors in this collection also acknowledge the difficulties of this task, and the discomfort it involves on both sides. Including a special prologue by the novelist Leila Aboulela, this collection deals with the politics of Muslims' representation and identity formation in media, cinema, literature and political dialogue, from the crusades through to the twenty-first century.